Pengaruh Motivasi Orang Tua Terhadap Prestasi Belajar Siswa Kelas V SD Gugus II - Mujahidah Mujahidah; Mutmainnah Isnar; Abd Kadir A; Rahmawati Patta (Universitas Negeri Makassar, 2021)
The problem in this study is the lack of parental motivation for children's learning so that children are less enthusiastic about learning. This research is a descriptive quantitative research with a correlation design which aims to determine the effect of parents' motivation on the learning achievement of fifth grade elementary school students in Cluster II. The results showed that there was an effect of parental motivation on the learning achievement of fifth grade elementary school students in Gugus II, Tanete Riattang District, Bone Regency with a tcount value (6.6949) greater (>) ttable value (1.66691) which means H0 is rejected and H1 is accepted. . Based on the analysis of the data above, it can be concluded that the motivation of parents and student achievement in the school is carried out well and there is an influence between the two variables. From these conclusions, the impact resulting from this study is the influence of parental motivation on student achievement, it is known that good parental motivation will increase student achievement.